A boundary element method for a second order elliptic partial differential equation with variable coefficients - Ang, W.T.; Kusuma, J.; Clements, D.L. (Elsevier Ltd., 1996)
A boundary element method is derived for solving a class of boundary value problems governed by an elliptic second order linear partial differential equation with variable coefficients. Numerical results are given for a specific test problem.